Characterization of the Genetic Defects in Recessive Type 1 and Type 3 von Willebrand Disease Patients of Italian Origin - Eikenboom, Jeroen C. J.; Castaman, Giancarlo; Vos, Hans L.; Bertina, Rogier M.; Rodeghiero, Francesco (Thrombosis and Haemostasis, 1998)
The genetic defects causing recessive type 1 and type 3 von Wille-brand disease (VWD) in eight families from the northern part of Italy have been investigated. Mutations were identified in 14 of the 16 disease-associated von Willebrand factor (VWF) genes. Only one mutation, a stop codon in exon 45, was previously reported. Several new mutations were identified: one cytosine insertion in exon 42, one guanine deletion in exon 28, one probably complete VWF gene deletion, one substitution in the 3’ splice site of intron 13, one possible gene conversion, and three candidate missense mutations. One missense mutation, the substitution of a cysteine in exon 42, was identified in all type 3 VWD patients that were previously characterized as a subgroup with significant increase of factor VIII procoagulant activity after desmopressin infusion. This paper demonstrates again that the molecular defects of quantitative VWD are diverse and located throughout the entire VWF gene.